Hybrid bio-composites reinforced with natural wood saw dust and eco-friendly graphite: evaluation of physical, mechanical, and thermal properties - Vengadesan, Elumalai; Arunkumar, T.; Muralidharan, S.; Debnath, Kishore; Dutta, Hrishikesh; Kadirgama, Kumaran (The Korean Fiber Society, 2025)
Natural fller-reinforced PLA composites are a sustainable alternative to petroleum-based polymers in industries such as automotive, consumer products, packaging, aerospace, sports, and electronics. However, they have poor performance in humid environments due to the hydrophilic nature of fllers. Graphite is an efective reinforcement to improve the strength and hydrophobic nature of composites. Therefore, this study explores the efects of reinforcing graphite (5–20%) on the properties of PLA composites reinforced with waste sawdust (10–30%). The mechanical, thermal, and water absorption properties of injection mold samples are evaluated following ASTM standards. The mechanical and thermal properties of graphite-reinforced composites outperformed those of neat PLA and sawdust-reinforced composites (SDC) due to their higher rigidity, thermal conductivity, and nucleation efect on the composites. HC2 (10% graphite) achieves peak tensile and fexural strengths of 54 and 145 MPa, surpassing PLA by 237.5 and 241.2%, and SDC by 10.6 and 25%, respectively. Furthermore, peak compressive strength and hardness of 82.33 MPa and 84 are obtained for HC2. However, excessive graphite reduces the impact strength of HCs due to stress concentration and brittleness. The crystallization and thermal stability are also improved due to the nucleation efect of SD and graphite in the HCs. Moreover, the water absorption of HCs is lower than that of SDC by 9.2–32.7%, indicating the efectiveness of hydrophobic graphite reinforcement. The measured results reveal that the addition of graphite as secondary reinforcement in HCs enhances the mechanical and thermal properties of the composites while reducing water absorption.